No-take marine reserves control the recovery of sea urchin populations after mass mortality events. (March 2019) - Medrano, Alba; Linares, Cristina; Aspillaga, Eneko; Capdevila, Pol; Montero-Serra, Ignasi; Pagès-Escolà, Marta; Hereu, Bernat
Abstract: Understanding how no-take zones (NTZs) shape the population dynamics of key herbivores is crucial for the conservation and management of temperate benthic communities. Here, we examine the recovery patterns of sea urchin populations following a high-intensity storm under contrasting protection regimes in the NW Mediterranean Sea. We found significant differences in the recovery trends of Paracentrotus lividus abundance and biomass in the five years following the storm. The P. lividus populations outside the NTZ recovered faster than the populations inside the NTZ, revealing that predation was the main factor controlling the sea urchin populations inside the NTZ during the study period. Arbacia lixula reached the highest abundance and biomass values ever observed outside the NTZ in 2016. Our findings reveal that predation can control the establishment of new sea urchin populations and emphasize top-down control in NTZs, confirming the important role of fully protected areas in the structure of benthic communities. Highlights: Top-down controls are the main force controlling the recovery of depleted herbivorous populations. Fully protected areas have an important role in the recovery patterns of sea urchin populations. Well-designed long-term monitoring is key for a better understanding of the natural dynamics of benthic populations.